Psychosocial risks - Raffo Lecca, Eduardo (2013)
The article reviews the concepts of the unfinished in Occupational Risk Prevention (PRL): Psychosocial risks, thus finding that each day is increasing its importance on the health of workers and organizations (INSL). The study concludes that the laws of Safety and Health at Work in Peru, to promote a culture PRL, as shown in the good intentions of its articles. That is not enough to promote, it is also important to identify and evaluate the PRL. The laws and regulations and annexes suffer from methodological guidelines on how to act in the identification and assessment of psychosocial risks.